Analysis of Online Registration Service Quality on the Satisfaction of BPJS Outpatients with the Mediation of Perceived Ease of Use at RSUD Ciamis - Yulianti, Elys; Windiyaningsih, Cicilia; Supardjo, Supardjo (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the influence of online registration service quality on the satisfaction of BPJS outpatients at RSUD Ciamis, with perceived ease of use as a mediating variable. The research is motivated by the low utilization of the online registration system, despite RSUD Ciamis implementing two digital platforms: RSUD Ciamis Mobile (June 2023–May 2024) and JKN Mobile (June 2024–present). Challenges such as limited registration quotas, disorganized queues, and the dominance of elderly patients preferring onsite registration serve as the main focus of this research. A quantitative approach was employed with a cross-sectional survey design. The sample consisted of 96 BPJS outpatients who had used online registration, selected through quota sampling. Data were analyzed using multiple linear regression and the Sobel test. The results reveal that online registration service quality significantly affects perceived ease of use and patient satisfaction. Moreover, perceived ease of use has a significant direct effect on satisfaction and serves as a significant mediator between service quality and patient satisfaction. These findings emphasize that perceived ease of use is a crucial determinant in optimizing patient experiences with digital health services. The study recommends strengthening patient education, developing elderly-friendly features, and conducting regular evaluations of digital system effectiveness to ensure sustainable improvements in service quality.